(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: The main aim of the study was to identify the development of antimicrobial susceptibility and resistance in Extended-Spectrum Beta-Lactamase (ESBL) producing E. coli. that cause UTI and to determine suitable antibiotic choices in the said organisms. Methodology: It was a Cross-sectional retrospective study, where 200 clinical uropathogenic E. coli isolates were picked and assessed antimicrobial resistance by the Kirby buyer method and confirmation was performed using a double disc synergy test to detect ESBN producers. Findings: The paper illustrates that females (82%), adults (50%), have a high risk of developing such infections because of several changes in the anatomy and behaviours. Imipenem, amikacin, Fosfomycin and tazobactam/piperacillin possess 98.5, 91.0, 84.5 and 86 patterns of sensitivity to E. coli isolates collected and thus can be used as a choice of treatment against UTIs caused by E. coli 46/65 65 E. coli isolates were found to be multidrug-resistant by initial screening of antimicrobial susceptibility test and therefore confirmed to be 60.7. Conclusion: It was ascertained that although the E. coli has since developed resistance to many of the medicines yet there are a few antibiotics that can be considered when writing the prescription. These infections are more prevalent among women and adults, and they should be educated adequately to avoid them.